A política externa do Vaticano e o conflito Israel-Palestina: Um estudo sobre as políticas de Pio XII até Francisco - Teixeira, Clara Nogueira Biscaro (2024)
The present work aims to analyze the Vatican's foreign policy regarding the Israel-Palestine conflict and to conduct a descriptive study on the actions taken from the pontificate of Pius XII (1939 – 1958) to Francis (2013 – present), including John XXIII (1958 – 1963), Paul VI (1963 – 1978), John Paul II (1978 – 2005), and Benedict XVI (2005 – 2013). The study is based on documentary analysis, focusing on the official documents and statements of the studied states and multilateral organizations, as well as specific bibliography on the subject and related issues. Additionally, it employs the constructivist approach of International Relations to establish the factors that led to such evident changes in positions, given that Pius XII is known for his public omission regarding the Jews and the formation of the State of Israel, while Francis operates within a context of formal bilateral relations with both Israel and Palestine, as well as the recognition of these as States. Preliminarily, it is observed that there are indeed changes in the conduct of foreign policy, and the factors highlighted for such changes begin with the break during the papacy of John XXIII and the convening of the Second Vatican Council. From this point on, subsequent popes adopted a model of foreign policy characterized by openness to other non-Christian religions, which began to permeate bilateral relations between Israel and the Vatican, and concurrently, with Palestine.